Komunikasi Manajemen Sumber Daya Manusia (SDM) di UPT Puskesmas Alahair Kabupaten Kepulauan Meranti, Selatpanjang - alendra, verani; Hartono, Budi (Komunika : Jurnal Ilmiah Komunikasi, 2023)
Puskesmas is a technical implementation unit of the District or City Health Service which is responsible for implementing health development in a health area. HR management is important in carrying out activities at the Puskesmas. This article aims to find out the importance of HR management, especially at the Puskesmas. The method used is the identification of previous articles with a total of 10 articles and a span of 10 years (2013-2023). The results show that good human resource management influences the achievement of organizational goals by increasing performance.